Pengaruh Metode Latihan Interval Anaerob ATP-PC Terhadap Peningkatan Vo₂max pada Atlet Lari Sprint IKIP PGRI Pontianak: Nevi Hardika, Syarif Musa - Syarif Musa; Nevi Hardika (Journal Sport Academy, 2022)
The purpose of writing is to find out the improvement VO₂ max after training ATP-PC Anaerobic Interval for sprint athletes from IKIP PGRI Pontianak. The method used in this research is quantitative with the type of experimental research (True Experimental research) with a one group pre-test – post-test only design. The technique used to collect data in this research is Test and Measurement technique using Multistage Fitness Test (MFT). The sample selection carried out in this study was by Proportional Random Sampling that is, the proportional number of members from each prenatal is taken. So the number of samples for Anaerobic ATP-PC training is 20 athletes. The data analysis technique used in this study used Paired T-Test at = 0.05. The results of the study concluded there is an increase in the Maximum Oxygen Volume (VO₂ max) significant So that it can be applied interval training, athletes can have and increase the capacity of Maximum Oxygen Volume (VO₂ max) so that it can prepare the physical condition (durability) in the ATP-PC anaerobic system exercise with direction and training.